Effects of the interference of L1 on L2 concerning speaking in first year students of the Foreign Language Department - Ascencio Vides, Roxana Guadalupe; Escobar González, Verónica Emperatríz; Parada Ramírez, Cecilia María; Alvarado, José Matthew; Ayala, Edgar Nicolas (San Salvador El Salvador : Universidad de El Salvador, 2014)
Students who start studying the Licenciatura en Idioma Inglés Opción Enseñanza face a big challenge: to communicate both orally and writing. In attempting to do this many of them fall into the temptation of using their L1 which in the long run affects their attempt because they end up being misunderstood, or what is worse: zero communication. This situation can be seen, when these students try to speak in the target language either inside or outside the class; for them it is difficult to hold a conversation without using the mother tongue (L1), this way it is observed that in a conversation come up phrases like: “she said me”, “I have hungry”, “I have 20 years old”, etc. The need that students find to resort to the L1 when speaking the L2 is classified as a positive, negative and zero interference or transfer. It is understood by positive interference or positive transfer the fact that the students use the structures already existing in their mother tongue and that with very slight adjustments they can be transferred to the L2. For example, “This organization is a non-profit foundation”. (In L1 it means: Ésa organización es una fundación no lucrativa). There are 2 words with similarity in both languages, in Spanish and English; “Organisation-Organización” and “Foundation-Fundación”. In interference or negative transfer, the structures are different in both mother tongue and target language; for example, “Actually, my dear Steven. This one is the exit”. (In L1 it means: De hecho, mi querido Steven, ésa es la salida). There are 2 words with similarities in writing, but different meaning. In L1 the word “Actually” means “De hecho”. Finally it is the zero interference, when there is not effect between L1 and L2, the switch is spontaneous and natural. For example: “The green apple is mine”. In this phrase the meaning in both language (Spanish and English) there is not interference.
Anexos.
Tesis para optar al título de -- (Licenciada en Lenguas Modernas Especilidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2014
Bibliografía : hojas 37-38
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza